Modified silica gels as recyclable adsorbents of aqueous polycyclic aromatic hydrocarbons. Issue 4 (2nd October 2019) - Regan, John; Dolores, Jessi; Lepore, Megan; Gualano, Michael; Badson, Jeovanna; Zimnoch, Amanda; Capitani, Joseph F.; Fan, Jianwei
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs), a class of toxic organic molecules containing multiple fused aromatic rings, are found in air, soil and water as a by-product from the incomplete combustion of organic matter. We report on the modification of silica gel using lipophilic molecules containing carboxylic acids, for anchoring to the surface via hydrogen bonds. The lipophilic component captures aqueous PAH, specifically phenanthrene, through the agency of π–π and π–sp 3 interactions. The structure–sorption-relationships suggest optimum phenanthrene adsorption is achieved with unsaturated bonds in linear chains or two phenyl rings. Examples include linoleic acid or 2, 3-diphenylpropionic acid with removal values of 281 and 283 ng PAH per gram of silica gel, respectively. Saturation adsorption is achieved within four hours. Proposed modes of binding of the new reverse phase silica gels with phenanthrene are described. Recycling of the silica gel is accomplished by washing with organic solvents to remove PAH. GRAPHICAL ABSTRACT: